Pengaruh Inflasi Terhadap Capaian Ekspor Komoditas Migas di Indonesia (Studi pada Tahun 2020-2023) - Riyadi, Oky Andrian; Arif Nugrahanto (Polytechnic of State Finance STAN, 2024)
Several studies regarding the influence of inflation on export performance have reached relatively similar conclusions. Lovasy (1962) found evidence that inflation tends to inhibit export expansion. Gylfason (1999) further strengthened this, specifying that high inflation in natural resource commodities tends to be associated with low export levels. Given Indonesia's status as an oil-exporting country, researchers were interested in conducting statistical testing in the Indonesian context using data from the Ministry of Trade and the Central Statistics Agency for the period 2020-2023. The research approach adopted in this study follows Tien (2021) using IBM Statistics SPSS 25 software for data processing. The dependent variable is the export of oil commodity, while the independent variable is the inflation rate. The results of regression indicate that the coefficient of determination between variables has a statistically significant value to reject the null hypothesis. This suggests that the inflation rate has a positive impact on oil export performance. The positive impact of inflation on oil commodity export performance may be attributed to several factors, including world oil market conditions, domestic economic structure, and government export policies.